Associations of DNA Base Excision Repair and Antioxidant Enzyme Genetic Risk Scores with Biomarker of Systemic Inflammation - Mao, Ziling; Gray, Abigail L. H.; Gross, Myron D.; Thyagarajan, Bharat; Bostick, Roberd M. (Frontiers in Aging, 2022)
Background: Inflammation is implicated in the etiology of various aging-related diseases. Numerous dietary and lifestyle factors contribute to chronic systemic inflammation; genetic variation may too. However, despite biological plausibility, little is known about associations of antioxidant enzyme (AE) and DNA base excision repair (BER) genotypes with human systemic inflammation. Methods: We genotyped 22 single nucleotide polymorphisms (SNPs) in 3 AE genes, and 79 SNPs in 14 BER genes to develop inflammation-specific AE and BER genetic risk scores (GRS) in two pooled cross-sectional studies (n=333) of 30 – 74-year-old White adults without inflammatory bowel disease, familial adenomatous polyposis, or a history of cancer or colorectal adenoma. Of the genotypes, based on their associations with a biomarker of systemic inflammation, circulating high sensitivity C-reactive protein (hsCRP) concentrations, we selected 2 SNPs of 2 genes (CAT and MnSoD) for an AE GRS, and 7 SNPs of 5 genes (MUTYH, SMUG1, TDG, UNG, and XRCC1) for a BER GRS. A higher GRS indicates a higher balance of variant alleles directly associated with hsCRP relative to variant alleles inversely associated with hsCRP. We also calculated previously-reported, validated, questionnaire-based dietary (DIS) and lifestyle (LIS) inflammation scores. We used multivariable general linear regression to compare mean hsCRP concentrations across AE and BER GRS categories, individually and jointly with the DIS and LIS. Results: The mean hsCRP concentrations among those in the highest relative to the lowest AE and BER GRS categories were, proportionately, 13.9% (P=0.30) and 57.4% (P=0.009) higher. Neither GRS clearly appeared to modify the associations of the DIS or LIS with hsCRP. Conclusion: Our findings suggest that genotypes of DNA BER genes collectively may be associated with systemic inflammation in humans.